2017
DOI: 10.2147/tcrm.s144659
|View full text |Cite
|
Sign up to set email alerts
|

Decreased frequency of adenoidectomy by a 12-week nasal budesonide treatment

Abstract: ObjectiveThere is little evidence on the role of topical budesonide in reducing the frequency of adenoidectomy, although it was reported that topical budesonide can effectively ameliorate the symptoms of adenoid hypertrophy (AH). This study was aimed to investigate the possibility and safety of alternatives to adenoidectomy with a 12-week treatment with nasal budesonide.Materials and methodsOne hundred patients with AH were randomized to receive either a double-blind budesonide (1 mg once daily) or placebo tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…In the study by Hong et al, [115] all children in the treatment group showed a significant reduction in the nasal obstruction index (NOI) compared to controls. The significant difference of NOI between the two groups of children was confirmed after 12 weeks of open treatment (p < 0.001).…”
Section: Is Topical Treatment With Ics Indicated In Adenoid Hypertrophy?mentioning
confidence: 97%
See 1 more Smart Citation
“…In the study by Hong et al, [115] all children in the treatment group showed a significant reduction in the nasal obstruction index (NOI) compared to controls. The significant difference of NOI between the two groups of children was confirmed after 12 weeks of open treatment (p < 0.001).…”
Section: Is Topical Treatment With Ics Indicated In Adenoid Hypertrophy?mentioning
confidence: 97%
“…Four 4 months later, 77.2% of subjects from the treated group were excluded from the surgery list, while all the non-treated subjects underwent surgery. The second study [115], is a double-blind trial which after the first 2 weeks shifted to an open study for 12 weeks. Fifty children aged 6-8 years, with AH grade > 2 and AHI > = 2/h, were treated with budesonide and 50 children used physiological solution.…”
Section: Is Topical Treatment With Ics Indicated In Adenoid Hypertrophy?mentioning
confidence: 99%
“…Операції на аденоїдах і мигдаликах належать до дуже поширених, проте останнім часом їхня частота зменшилася з появою альтернативних методів лікування разом із наявними короткотерміновими ризиками хірургічного лікування [4,14,20,30,43,54,79]. Можна обміркувати призначення медикаментозного лікування, яке є альтернативою хірургічному, безпечним і надає тривале полегшення при обструкції верхніх дихальних шляхів [48].…”
Section: як лікувати аденоїди без операції?unclassified
“…Деякі дослідження довели, що будесонід пригнічує проліферацію лімфоїдної тканини in vitro у дітей з ОСАС, а 6-тижневе лікування ендоназальним будесонідом ефективно зменшує важкість ОСАС [54,55]. Проте невідомо, чи довготривале лікування ендозанальним будесонідом, який має істотну системну біодоступність, може вплинути на ріст дітей і зменшити частоту операцій серед дітей з ГА [48]. Ендоназальний беклометазон також має високу системну біодоступність, що не дає можливості призначати його довшим курсом та маленьким дітям з огляду на високий ризик системних побічних ефектів.…”
Section: велика ліпофільність фуроату → максимум місцевої дії + відсуunclassified
“…Adenoid hypertrophy can lead to the nasopharynx obstruction and cause symptoms including snoring, Rhinorrhea, nasal congestion, mouth breathing, halitosis, hyponasal speech, restless sleep, hypersomnolence, and enuresis. It also plays an important role in chronic rhinosinusitis and middle ear infection with effusion (6). In most cases, the removal of a local reservoir of pathogenic microbiota such as adenoid and tonsils decreases the clinical signs and symptoms of affected patients (7).…”
Section: Introductionmentioning
confidence: 99%